PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASI - Widya Utami Lubis; Zulkarnain Zulkarnain (Jurnal Penelitian Bimbingan dan Konseling, 2018)
This study aims to determine the influence of transformational leadership and the quality of work life to organizational commitment. The study involved 200 employees plantation. Data were collected by using scales of transformational leadership, quality of work life and organizational commitment. The data analyzed by multiple linear regression. The results showed that transformational leadership and quality of work life influenced significantly toward organizational commitment (R= 0.480, = 0.230, F= 29.484; P<0.01). Transformational leadership and the quality of working life made a significant contribution to the improving of employees' organizational commitment. Results of this study are expected to provide an understanding of how transformational leadership and quality of work life influence organizational commitment of employees, and also provide an insight to the company about the level of organizational commitment of employees, employees perceptions about the role of transformational leadership as well as an overview about quality of working life of employees. Keywords : transformational leadership, quality of work life, organizational commitment, plantation employee.